Analisis Campur Kode dan Alih Kode dalam Perayaan Liturgis di Kapela St. Yohanes Paulus Ii Maudemu - Maternus Mali; Yohanes Rusae; Hironimus Taolin (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study was motivated by a sociolinguistic phenomenon in the Indonesia–Timor-Leste border area, particularly at St. John Paul II Maudemu Chapel, Belu Regency, where the incorporation of the Bunaq language into Catholic liturgy enhances the congregation’s participation and understanding. The study aimed to identify the forms, contributing factors, and functions of code-switching and code-mixing in liturgical communication. A descriptive qualitative approach was employed. Primary data were collected through direct observation of Sunday liturgical celebrations and structured in-depth interviews with eleven informants, including the parish priest, catechists, Basic Ecclesial Community leaders, community representatives, and Catholic youth members. Secondary data were obtained from books, journal articles, and Church documents. Data were analyzed through data collection, reduction, display, and conclusion drawing. The findings reveal that code-switching between Indonesian and Bunaq occurs during the homily, liturgical announcements, and prayers of the faithful, while code-mixing appears through the use of Bunaq kinship terms and culturally significant expressions. These linguistic practices are influenced by the congregation’s limited understanding of formal Indonesian religious terminology, the priest’s pastoral communication strategies, and the need to create a more familiar liturgical atmosphere. The use of both languages strengthens comprehension of Scripture, increases spiritual engagement, and supports the preservation of Bunaq cultural identity through liturgical inculturation.